Spinning starlight - Lewis, R. C. (Rachel Christine), 1979- (Hyperion, 2015)
"Sixteen-year-old heiress and paparazzi darling Liddi Jantzen must save her brothers in this outer-space retelling of Hans Christian Andersen's The Wild Swans"--